2015
DOI: 10.1016/j.ygeno.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequences and comparative genome analysis of Lactobacillus plantarum strain 5-2 isolated from fermented soybean

Abstract: Lactobacillus plantarum is an important probiotic and is mostly isolated from fermented foods. We sequenced the genome of L. plantarum strain 5-2, which was derived from fermented soybean isolated from Yunnan province, China. The strain was determined to contain 3114 genes. Fourteen complete insertion sequence (IS) elements were found in 5-2 chromosome. There were 24 DNA replication proteins and 76 DNA repair proteins in the 5-2 genome. Consistent with the classification of L. plantarum as a facultative hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 51 publications
4
53
1
1
Order By: Relevance
“…However, among these predicted prophages, many elements were lost. For example, a significant component integrase (a marker for mobile DNA elements and participating in bacteria pathopoiesis (Liu et al, ) was not predicted in any of the above prophages.…”
Section: Resultsmentioning
confidence: 99%
“…However, among these predicted prophages, many elements were lost. For example, a significant component integrase (a marker for mobile DNA elements and participating in bacteria pathopoiesis (Liu et al, ) was not predicted in any of the above prophages.…”
Section: Resultsmentioning
confidence: 99%
“…The sodium/proton (Na + /H + ) reverse transporter on cytoplasma membrane is the main way of microbial efflux of Na + , which regulates intracellular pH homeostasis (Padan et al 2005). It has been reported that L. plantarum 5-2 genome contained eight genes encoding the Na + /H + antiporters (Liu et al 2015). In this study, comparative genomic analysis revealed at least ten, nine, and six genes encoding Na + /H + antiporters in L. plantarum D31, T9, and ST-III genomes, respectively.…”
Section: Strain-specific Genes In L Plantarum D31 and T9 Genomesmentioning
confidence: 99%
“…This redundancy may contribute to its ability to grow in complex microbial ecosystems [173]. With regard to gene products, the L. sakei genome shares the highest level of conservation with Lactobacillus plantarum, which can be used as a starter in fermented meat, dairy, and vegetable products [144,174,175]. Genome analysis revealed a specialized metabolic repertoire to adapt and grow on meat products.…”
Section: Omics Of Meat Starter Culturesmentioning
confidence: 99%